Antiviral efficacy of molnupiravir versus ritonavir-boosted nirmatrelvir in patients with early symptomatic COVID-19 (PLATCOV): an open-label, phase 2, randomised, controlled, adaptive trial - Schilling, WHK; Jittamala, P; Watson, JA; Boyd, S; Luvira, V; Siripoon, T; Ngamprasertchai, T; Batty, EM; Cruz, C; Callery, JJ; Singh, S; Saroj, M; et al. (Elsevier, 2023)
Background: Molnupiravir and ritonavir-boosted nirmatrelvir are the two leading oral COVID-19 antiviral treatments, but their antiviral activities in patients have not been compared directly. The aim of this ongoing platform trial is to compare different antiviral treatments using the rate of viral clearance as the measure of antiviral effect.